THE INFLAMMATORY STATUS AND LYMPH NODE METASTASES IN NON-SMALL CELL LUNG CANCER - D. S. Pismenny; O. E. Savelieva; M. V. Zavyalova; E. O. Rodionov; L. A. Tashireva; S. A. Tuzikov; O. V. Pankova; V. M. Perelmuter (Сибирский онкологический журнал)
Introduction. The development of inflammation is characterized by changes in blood hematology parameters and indices. Various inflammatory parameters are used to assess the inflammatory status (IS) during cancer treatment. Recent studies have revealed a relationship between tumor progression and the presence of chronic inflammation. Consequently, there have been many attempts to predict the risk of tumor recurrence and distant metastases, as well as patient’s survival assessing the various inflammatory markers. The relationship between IS parameters and lymph node metastasis remains poorly understood in non-small cell lung cancer (NSCLC).Material and Methods. The prospective study included 35 patients with NSCLC (T1–4N0–2M0). Seventeen patients received 2–3 cycles of neoadjuvant chemotherapy (NAC). A leukocyte formula was determined in the peripheral blood and inflammatory indices, such as neutrophils to lymphocytes ratio (NLR), platelets to lymphocytes ratio (PLR), lymphocytes to monocytes ratio (LMR) and systemic immuno-inflammatory index (SII) were calculated. In addition, the concentrations of fibrinogen, C-reactive protein (CRP) and cortisol were evaluated.Results. NAC alone did not significantly change the parameters of patients’ IS. Lymph node metastases were associated with changes in parameters indicating the enhanced IS. In the group of patients who did not receive NAC, lymph node metastasis was associated with fibrinogen blood levels (cut-off value 5.35 g/L), PLR index value (cut-off value 7.18) and cortisol blood concentration (cut-off value 414 nmol/mL). The confidence level was χ2 =10.118; р=0.018. In the group of patients who received NAC, lymph node metastasis was associated with the leukocyte count (cut-off value 7.1×109 /L), PLR index value (cut-off value is 7.18) and CRP blood concentration (cut-off value is 8.5 mg/L). The confidence level was χ2 =8.193; р=0.042.Conclusion. Risk of lymph node metastasis in NSCLC is associated with IS. Parameters of IS can be used to predict the risk of lymph node metastases.